Pengaruh Metode Tugas, Ceramah, dan Diskusi Terhadap Pemahaman Materi Akuntansi pada Mahasiswa Universitas Muhammadiyah Surakarta 2021: Studi Kasus - Mahsa, Almira Ayudia; Isa, Muzakar; Fahd, Mohammed (Journal of Economics and Management, 2024)
This research aims to determine the effect of the assignment method, lecture method, and discussion method on the level of understanding of lecture material among accounting students at the Muhammadiyah University of Surakarta class of 2021. This research is motivated because the lecture method and assignment method are considered not to influence the level of understanding, while the discussion method does. level of understanding. This type of research is descriptive quantitative research. The population in this study was UMS accounting students Class of 2021, totaling 515 people. Based on the population, the sample taken was 34 people. The type of data used is primary data collected using questionnaire techniques. The research results show that: 1) t count (Task Assignment Method) 2.226 > 2.032; 2) t count (Lecture Method) 0.735 < 2.032; and 3) t count (Discussion Method) 3.415 > 2.032. The conclusion is that there is an influence between the assignment method and the discussion method on the level of understanding of lecture material among UMS Class of 2021 accounting students, while the lecture method has no influence.